Solves Transportation Troblems Using MATLAB - Souksomvang , Phoui; Boualakham, Sengdala (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
In the linear problem of programming, the mathematical model of the transport problem is the basis for solving many real-life problems related to optimization problems. It is clear that in the past many mathematicians have tried to find solutions to the transportation problem to get the best answer. Those methods include the Northwest Corner Rule, the Least Cost Method, Vogel’s Approximation Method, and the Modi method, but now most researchers use manual computation or a built-in program such as LINDO, QM or EXCEL to help you figure out the solution. On the other hand, if we use coding in MATLAB to solve the problem, it will give us a deeper understanding of the various stages of the search for the outcome of the problem, and it also helps to solve the problem in case the matrix of costs is much larger. Therefore, in this study, the author will use coding in MATLAB to solve transportation problems with the goal of solving transportation problems according to the Northwest Corner Rule, Least Cost Method, Vogel’s Approximation Method, and Modi method.